Effects of powder size of interface material on selective hybrid carbon microwave joining of SS304–SS304. (January 2017) - Bagha, Lucky; Sehgal, Shankar; Thakur, Amit; Kumar, Harmesh
Abstract: Effects of powder size of interface material on physical and mechanical properties of selective hybrid carbon microwave joining based SS304-SS304 welded joints have been investigated. SS304 specimens have been joined with Nickel as interface material. Four types of joints have been fabricated and studied by using interface material of 50 μm, 40 μm, 30 μm and 20 μm size. Welding joints have been characterized physically through scanning electron microscope, energy dispersive spectroscopy and mechanically through Vickers micro hardness test and micro tensile test. Physical test results revealed that homogeneity of joint increased with decrease in Nickel powder size. Hardness tests confirmed a linear increase in hardness from heat affected zone to bead centre for all the joints. Joints with Nickel powder of smaller grain size resulted in harder welding beads. Smaller powder size also helped in obtaining better tensile strength of joint but with reduced ductility.